The Influence of Work Motivation and Knowledge on Organizational Citizenship Behavior of Kindergarten Teachers in Bogor City - Griet Helena Laihad; Eka Suhardi (International Publisher (YAPENBI), 2023)
The purpose of this research is to examine the influence that kindergarten teachers' levels of motivation and knowledge have on their levels of organisational citizenship behaviour (OCB). A questionnaire was given to a random sample of eighty kindergarten instructors living in Bogor City as part of the research. A series of surveys were used to collect the data, which was followed by analysis utilising procedures including multiple linear regressions. The findings indicated that OCB in kindergarten instructors was significantly affected by both a teacher's level of knowledge and motivation. Because OCB has a positive relationship with motivation and knowledge, this indicates that the level of OCB displayed by a teacher is proportional to the level of motivation and knowledge displayed by that instructor. These findings may have substantial ramifications for education administration and policy makers, with the potential to raise the knowledge and motivation of kindergarten teachers, hence improving teacher performance and fostering a more positive work atmosphere in schools.